Tiktok Marketing as a Digital Branding Strategy in Response to change in Generation Z Consumer Behavior - Hatma Aura Rahmah; Tamamudin Tamamudin (Journal Social Society, 2026)
The development of digital technology has transformed marketing strategies toward experience-based digital branding, with TikTok emerging as a dominant platform among Generation Z. In Indonesia, the large population of Generation Z makes TikTok a strategic medium for digital marketing through influencer collaborations, viral challenges, and user-generated content. However, existing studies largely focus on quantitative indicators and provide limited insight into consumers’ subjective experiences.This study aims to explore how Generation Z interprets and responds to TikTok marketing strategies as a form of digital branding. A qualitative phenomenological approach was employed by conducting in-depth interviews with 10–15 Generation Z informants aged 18–25 who actively use TikTok and engage with brand content, supported by non-participant observation. Data were analyzed using thematic analysis. The findings indicate that TikTok marketing significantly influences Generation Z’s consumption behavior, particularly through viral content and influencer trust. High levels of engagement enhance brand awareness and emotional attachment, while repeated exposure to trends encourages impulse buying and consumption as a form of social identity. These results highlight TikTok’s effectiveness as a digital branding platform and offer practical implications for brands and MSMEs in developing authentic and engaging marketing strategies.